Kajian Literatur Terhadap Fatwa Ajaran Waḥdah al-Wujūd Berdasarkan Beberapa Karya Popular Alam Melayu di Malaysia: Wahdah al-Wujūd’s Teachings Fatwas on Popular Manuscripts of Malay Archipelago: A Literature Review - Hj Mat Jusoh, Mohd Zulfakar; Sa’ari, Che Zarrina; Zainal Abidin, Azmil (Al-Basirah Journal, 2022)
The doctrine of waḥdah al-wujūd constitutes a polemic that emerged within the field of Sufism. This controversy gave rise to both supporting and opposing groups. The opposing group took the initiative to issue fatwas declaring it prohibited. These fatwas are seen as imposing restrictions on several popular turāth works in Malaysia, preventing their dissemination and study. Meanwhile, the supporting group attempts to deny that the concept of waḥdah al-wujūd in those works reflects the misunderstood notions of ḥulūl (indwelling) and ittiḥād (union). This article aims to examine the fatwas concerning several popular turāth works alleged to contain the doctrine of waḥdah al-wujūd in Malaysia. These works have also been officially gazetted by State Islamic Religious Councils in Malaysia on the grounds that their teachings contain elements of waḥdah al-wujūd associated with ḥulūl and ittiḥād, which are considered to lead to disbelief. The article employs a qualitative research method through content analysis of documents and historical review of the fatwas’ contents to elaborate on the reasons behind the rulings that led to the prohibition of waḥdah al-wujūd teachings in Malaysia. The findings conclude that the first fatwa issued by the Johor State Islamic Religious Council, influenced by Sayyid Alawi Tahir al-Hadad, became the reference point and was followed by the majority of subsequent fatwas issued by several State Islamic Religious Councils in Malaysia.